Estudo de Marcadores Químicos de Ambrosia artemisiifolia L (Asteraceae) - Valdivino , Hyelen Bezerra Gouvea (2005)
Ambrosia artemisiifolia L. (Asteraceae) is a annual specie, normally considered a weed, that grows well in tropical areas, including the Amazon region. It is popularly known in Brazil as “catinga-de-bode”, “artemisia”, “arquemijo” and “artemija”. Traditionally, the tea of A. artemisiifolia. leaves is used for the treatment of stomach illness. This work describes the isolation of the sesquiterpene lactones, ambrosin and damsin, for the first time in this specie. Aqueous and chloroform extracts were evaluated in three different models of gastric lesions (ethanol, stress and indomethacin) induced acutely and showed significant protective activity. Chromatographic fingerprints of aqueous and chloroform extracts by high performance liquid chromatography and also essential oil analysis by high resolution gas chromatography were obtained from four different individuals collected in different locations in the Amazon region, Iranduba (AM), Juruti (PA), Manaus (AM) and Itacoatiara (AM), in order to develop chromatographic methods to be used in the quality control of the isolated chemical markers, accordingly to the resolution RDC N. 48.